2021
DOI: 10.1002/cbin.11657
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from human umbilical cord mesenchymal stem cells inhibit ROS production and cell apoptosis in human articular chondrocytes via the miR‐100‐5p/NOX4 axis

Abstract: Cyclic strain‐induced chondrocyte damage is actively involved in the pathogenesis of osteoarthritis and arthritis. MicroRNAs (miRNAs) carried by exosomes have been implicated in various diseases. However, the role of miR‐100‐5p in cyclic strain‐induced chondrocyte damage remains to be elucidated. miR‐100‐5p and NADPH oxidase 4 (NOX4) were silenced or overexpressed in human primary articular chondrocytes. PKH‐67 Dye was used to trace exosome endocytosis. Reactive oxygen species (ROS) production was monitored us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Researchers found that exosomes from UMSCs could inhibit cyclic strain-induced ROS production and apoptosis, which is an important cause of chondrocyte injury in OA. This might owing to exosomal miR-100-5p inhibiting the expression of NOX4 [ 162 ]. UMSCs-sEVs could also promote the polarization of M2 macrophages and the expression of IL-10, thereby regulating the immune level of OA to slow down cartilage degradation.…”
Section: 'Prohibitor'——evs As a Treatment Of Oamentioning
confidence: 99%
“…Researchers found that exosomes from UMSCs could inhibit cyclic strain-induced ROS production and apoptosis, which is an important cause of chondrocyte injury in OA. This might owing to exosomal miR-100-5p inhibiting the expression of NOX4 [ 162 ]. UMSCs-sEVs could also promote the polarization of M2 macrophages and the expression of IL-10, thereby regulating the immune level of OA to slow down cartilage degradation.…”
Section: 'Prohibitor'——evs As a Treatment Of Oamentioning
confidence: 99%
“…MiR-31-5p protects oxidatively stressed EPCs from ER-stress-induced apoptosis and calcification [15]. Through miR-100-5p, derived from hucMSCs-EXOs, targeting NADPH oxidase 4 (NOX4), it can inhibit apoptosis and reactive oxygen species (ROS) production in primary articular chondrocytes [16].…”
Section: Promoting Chondrocyte Migration Proliferation Hypertrophy An...mentioning
confidence: 99%
“…After BMSCs‐exo injection, the levels of inflammatory factors (TNFα, IL‐6) and chondrocyte apoptosis were reduced, the content of the main components of the ECM were increased in articular cartilage 135 . Moreover, numerous studies have shown great therapeutic potential of exosomes in inhibiting chondrocyte apoptosis with different mechanisms, and we present the details in Table 3 136–147 …”
Section: Apoptosismentioning
confidence: 99%
“…135 Moreover, numerous studies have shown great therapeutic potential of exosomes in inhibiting chondrocyte apoptosis with different mechanisms, and we present the details in Table 3. [136][137][138][139][140][141][142][143][144][145][146][147] Platelet-rich plasma (PRP) has often been considered as a potential candidate for OA, showing an excellent ability to inhibit chondrocyte apoptosis, but the results of a recent clinical trial do not support that PRP can be used as a drug for OA. 148,149 Confusingly, recent studies have confirmed that both PRP and PRP-derived exosomes (PRP-exo) can inhibit chondrocyte apoptosis, which has led to controversy over the therapeutic effects of PRP and PRP-exo.…”
Section: Exosomesmentioning
confidence: 99%